INTRUSIVE-MAGMATIC COMPLEXES OF WILHELM ARCHIPELAGO, WEST ANTARCTICA (PART 2 – HYPABYSSAL AND SUBVOLCANIC DYKE ROCKS) - Mytrokhyn, О.; Bakhmutov, V.; Gavryliv, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The second part of the work "Intrusive-magmatic complexes of Wilhelm Archupelago, West Antarctica" is devoted to dykes. The authors studied dyke rocks in the Ukrainian Antarctic Station area in order to specify their petrographic diversity as well as to clarify the spatial distribution of the dykes, their geological position, age and geological relationships with other igneous formations in the region. It was found that hypabyssal and subvolcanic dykes of the Mesozoic-Cenozoic age are widespread on the Wilhelm Archipelago. The most common composition are mafic and intermediate rocks namely microgabbros, diabases, basalts and microdiorites. Felsic dykes are subordinate. Typically, studied rocks occur as small dykes that can concentrate in extended swarms. Sill-like intrusions are less common. The spatial distribution of dykes is controlled by the Lemaer – Penola fault zone of northeastern strike. Their greatest concentration was found on the Argentine Islands. The geological relationships of the dykes with isotopically dated granitoids as well as the sequence of intrusion of individual dyke bodies, which is established in the places of their distribution, allowed to distinguish, at least, two stages of dyke formation - namely Mesozoic and Cenozoic. The most ancient dyke formations of the Argentine Islands are hypabyssal dykes and sill-like intrusions of the Mesozoic age. They intruded after the accumulation of the Jurassic-Cretaceous volcanic strata of the Argentine Islands, but before the formation of the Paleogene granitoids on the Barchans and Forge Islands. The petrographic diversity of Mesozoic dyke rocks is represented by microdiorites and microgabbros, as well as their contact-metamorphosed equivalents. All hypabyssal and subvolcanic dykes intruding the Paleogene granitoids on Barchans and Forge islands are of Cenozoic age. Among them, the most common are diabase and basalt dykes. Microdiorites are of subordinate importance. The characteristic petrographic features of the Cenozoic dykes allow to identify their age analogs outside of the Barchans-Forge granitoid intrusion.
Keywords: region; geology; dyke; hypabyssal and subvolcanic rocks